Major hazards of process equipment failures in the chemical process industry - Hussin, Nor Afina Eidura (2014)
Process equipment failures play significant roles in most accidents that occur and recur in the chemical process industry resulting in fire, explosion, and toxic release. In this study, 50 equipment-related accident investigation reports were used to analyze type and severity of incidents. The comprehensive accident report data were retrieved from U.S. Chemical Safety and Hazard Investigation Board (CSB) and U.S. National Transportation Safety Board (NTSB) accident databases with a mean year of 2005. Among the identified process equipment failures were piping systems (32%), storage tanks (20%), process vessels (16%), separation equipment (10%), reactors (8%), heat transfer equipment (8%), and others (6%). The analysis shows that 32% of the cases led to fire and explosion, followed by toxic release (26%), and explosion (22%) incidents. A total of 126 fatalities, 590 injuries, 260 exposures, four shelter-in-place, and 13 evacuations were reported. In most accident cases, fire, explosion, and/or toxic release incidents occur simultaneously. The synergy between major hazards results in catastrophic accidents with severe consequences in numbers of fatalities, injuries, exposures, shelter-in-place, and evacuations. To minimize the losses, plant and equipment should be designed and prepared for the worst-case scenario, not just adapting to any ‘applicable’ standards or guidance.